The Effects of Emotional Labor on Job Attitudes of Hotel Employees: Mediating and Moderating Roles of Social Support and Job Autonomy - IPLIK, Fatma Nur; TOPSAKAL, Yunus; IPLIK, Esengul (International Review of Management and Marketing, 2014)
With increasing competition among hotels, managing employees seems to be important issue in delivering services to customers effectively. This issue also affects the firms’ outcomes and incomes. Thus, hotels as service providing firms must be able to manage the emotions of employees in order to increase the quality of services and to create value for customers. Controlling emotions of employees also contribute to gain competitive advantage across rivals. The objective of this paper is to reveal the effects of emotional labor on job attitudes of hotel employees by considering the mediating and moderating roles of social support and job autonomy. To this end, a questionnaire was employed to employees of hotels operating in Antalya Province. Results of the analyses support that emotional labor has a negative effect on emotional exhaustion. Emotional labor also has a positive effect on job satisfaction. In addition mediating and moderating roles of job autonomy and social support between emotional exhaustion and emotional labor, and emotional labor and job satisfaction. Keywords: Emotional Labor; Job Satisfaction; Social Support; Job Autonomy; Hotels; Antalya. JEL Classifications: D23; L60; L84